2007
DOI: 10.1007/s11102-007-0031-0
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone levels in the diagnosis of growth hormone deficiency in adulthood

Abstract: Current guidelines for the diagnosis of adult growth hormone deficiency (GHD) state that the diagnosis must be proven biochemically by provocative testing that is done within the appropriate clinical context. The need for reliance on provocative testing is based on evidence that the evaluation of spontaneous growth hormone (GH) secretion over 24 h and the measurement of IGF-I and IGFBP-3 levels do not distinguish between normal and GHD subjects. Regarding IGF-I, it has been demonstrated that very low levels in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 101 publications
(141 reference statements)
1
14
0
Order By: Relevance
“…More recently, research has shown that cardiotoxicity is an unanticipated side effect of inhi- bition of c-Abl by imatinib [13] . On the other hand, the combined administration of GHRH with arginine recommended by the consensus guidelines [6] was beyond the scope of the present study. Instead, we used other established and reliable methods, including the GST and the L -dopa test, and IGF-I SDSs and IGFBP-3 SDSs.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…More recently, research has shown that cardiotoxicity is an unanticipated side effect of inhi- bition of c-Abl by imatinib [13] . On the other hand, the combined administration of GHRH with arginine recommended by the consensus guidelines [6] was beyond the scope of the present study. Instead, we used other established and reliable methods, including the GST and the L -dopa test, and IGF-I SDSs and IGFBP-3 SDSs.…”
Section: Discussionmentioning
confidence: 94%
“…IGF-I levels are a valuable biochemical marker of GH se-cretion. However, it is recommended that the diagnosis of adult GHD be confirmed by a provocation test of GH release [6] . Nearly 70% of these GHD patients showed severe deficiency on the GST.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patient characteristics can also influence accuracy of interpretation of GH provocation tests. Obese normal subjects have been shown to exhibit a blunted GH response to provocative stimuli to a degree that sometimes overlaps with the results obtained from severe GH-deficient adults (25). It has, therefore, been suggested that diagnostic cutoff criteria should be adjusted for body mass index to avoid the potential of a false-positive result.…”
Section: Implications For Practice and Researchmentioning
confidence: 99%
“…Known physiologic factors affecting the dynamic testing of GH secretion include gender, BMI, visceral adiposity, sex steroid status and age [159]. Responses to some secretagogues do not appear to attenuate with age [160].…”
Section: Adultsmentioning
confidence: 99%